Microencapsulation of ginger oil by complex coacervation using atomization: Effects of polymer ratio and wall material concentration - Ferreira, Sungil [UNESP]; Nicoletti, Vania Regina [UNESP] (Elsevier, 2021)
The objective of this work was to investigate the feasibility of inducing complex coacervation by atomizing an emulsion of gelatin/ginger oil over a gum Arabic solution, which would be a first step towards continuous process configuration. The influence of gelatin:gum Arabic ratio was investigated regarding capsule formation by atomization. In addition, the effects of emulsion concentration on coacervation by atomization and by batch stirring were studied. Gelatin:gum Arabic ratio strongly affected the capsule formation. The gelatin concentration affected the size of capsules for both methods, whereas the increase of gelatin concentration did not affect encapsulation parameters for atomized capsules. The diameter of microcapsules varied from 57 to 85 μm, encapsulation efficiency varied between 89.74 and 98.7%, and encapsulation yield ranged from 21 to 88%, with the atomization process resulting in higher encapsulation yield. The results indicated that microcapsules produced by atomization were comparable with capsules produced by batch stirring.
Keywords: Atomization; Complex coacervation; Encapsulation; Ginger oil; Ohnesorge number; Weber number